2020
DOI: 10.1016/j.jmapro.2020.01.032
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on girth friction welding of duplex stainless steel pipes

Abstract: Girth friction welding is a novel technique to join co-axial linepipes with an external ring (girth) in solid state and without melting of materials. The ring or the girth is rotated between two pipes under an axial force resulting in frictional heat generation and plastic deformation along the pipe-girth interfaces. The rotation of the girth is stopped after a preset displacement of the pipes while the force is maintained to consolidate the deformed material and form the joint along the girth-pipe interfaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This is because the higher upset time resulted in a predominant austenite phase with coarser grains. 11 For the optimized parameter, the hardness value is even low at PDZ due to higher upset time. 14 It has been observed by Chan et al 19 in their work that the microhardness was high for higher heat input.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This is because the higher upset time resulted in a predominant austenite phase with coarser grains. 11 For the optimized parameter, the hardness value is even low at PDZ due to higher upset time. 14 It has been observed by Chan et al 19 in their work that the microhardness was high for higher heat input.…”
Section: Resultsmentioning
confidence: 98%
“…Supplementary Figure 3 shows the survey of microhardness throughout the sample. Milton et al 11 reported that the DSS welds were softer than the base metal owing to their low ferrite proportion. In supplementary Figure 3 it is observed that the hardness values were lower in the weld zone for all three experiments compared to other zones PM and PDZ.…”
Section: Microhardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…3 d. The model showed a peak temperature of ~ 1537 K near the insert bottom, which is around ~ 93% of the solidus temperature of the DSS 2205. Kanan et al 26 and van Zyl et al 27 reported peak temperatures of around 91% and 90% of the substrate materials during FHPP. Higher peak temperature of the interface region aids towards the solid-state coalescence between the substrate and deformed material.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of computer technology, the numerical simulation of welding process provides a new way for the analysis of welding process and the optimization of welding process [16,17]. At the same time, many research institutions and researchers have done a lot of research on the shape of molten pool, residual stress, thermal cycle and deformation in the welding process of duplex stainless steel by numerical simulation technology [18][19][20][21]. At present, most studies mainly focus on the simulation of welding process between the same material of duplex stainless steel, while the simulation of welding between duplex stainless steel and dissimilar metal materials is rarely reported [22,23].…”
Section: Introductionmentioning
confidence: 99%